America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Fémininmasculin: le sexe de l'art. - Centre Georges Pompidou. (Passage du siècle, 1995)
Premier chapitre du Passage du siècle (les grands bilans que le Centre Georges Pompidou proposera en 1996 et 1997), cette exposition renoue avec des expériences décisives comme par exemple "Eros", organisée en 1959 par Marcel Duchamp et André Breton. A travers le titre "Féminin - Masculin, le sexe de l'art" s'exprime un double enjeu : celui de réhabiliter le terme dévalué d'une opposition inscrite dans la tradition des couples hiérarchiques de la pensée occidentale (forme/matière, vérité/mensonge, être/paraître, profondeur/surface, etc.) ; celui de montrer qu'au delà d'un simple sujet-motif artistique, le sexe est partie prenante des processus de l'art lui-même. L'ambition de cette exposition est de montrer, en dehors de toute approche chronologique, comment les productions artistiques du XXe siècle n'ont eu de cesse de venir brouiller les fatalités biologiques, anatomiques et culturelles traditionnellement liées au sexe. Aborder l'art dans la perspective de la différence sexuelle, ce n'est pas mécaniquement opposer un art "masculin" à un art "féminin", mais tenter de donner à voir comment les oeuvres se trouvent traversées par cette question, au-delà du sexe - du genre - des artistes qui les produisent. Féminin - Masculin, le sexe de l'art montrera aussi la coexistence dans ce siècle de deux généalogies artistiques concernant le sexe. L'une, à partir de Picasso, s'inscrit dans la tradition classique de la différence des sexes, conçue comme une opposition dialectique et organique du masculin et du féminin. L'autre, à partir de Marcel Duchamp, inaugure un nouveau type de relations, selon une logique asymétrique, faisant circuler les intensités masculines et féminines sur un mode proliférant qui opère une déterritorialisation des entités anatomiques, identificatoires et formelles. Les artistes de la jeune génération (tant américaine qu'européenne) semblent très sensibles à cette manière de déstabiliser les polarités traditionnelles du masculin et du féminin, mettant en oeuvre de nouvelles configurations éthiques et formelles qui se situent au-delà de la différence sexuelle, et en cela se distinguant en radicalement des positions identitaires des années 70.
Keywords: 1900-1999; LGBTQIA2+; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; exposition; har4600; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Moi, Tituba sorcière --: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Littératures et cultures, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques

Of woman born: Motherhood as experience and institution - Rich, Adrienne (Norton, 1995)
Adrienne Rich's influential and landmark investigation concerns both the experience and the institution of motherhood. The experience is her own—as a woman, a poet, a feminist, and a mother—but it is an experience determined by the institution, imposed on all women everywhere. She draws on personal materials, history, research, and literature to create a document of universal importance. Dans Of Woman Born , initialement publié en 1976, la poétesse et féministe influente Adrienne Rich examine les systèmes patriarcaux et les institutions politiques qui définissent la maternité. En explorant sa propre expérience - en tant que femme, poète, féministe et mère - elle trouve que l'acte de materner est à la fois déterminé par et distinct de l'institution de la maternité telle qu'elle est imposée à toutes les femmes partout dans le monde
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; corps; cours; discours dominant; fem1000; maternité; premier cycle; périodes historiques; régions géographiques; santé; systèmes d'oppressions; thématiques; théories féministes; états-unis

Defending pornography: free speech, sex, and the fight for women's rights - Strossen, Nadine (Scribner, 1995)
This book examines a key question that has divided feminists for decades: is censoring pornography good or bad for women? The book makes a powerful case that increasing government power to censor sexual expression, beyond the limits that the First Amendment sensibly permits (for example, outlawing child pornography) would do more harm than good for women and others who have traditionally been marginalized due to sex or gender. The book explains how the very anti-porn laws pushed by some feminists have led to the censorship of LGBTQ+ and feminist works, and it examines the startling connections between anti-porn feminists and right-wing fundamentalists. The book lays out the multiple current assaults on sexual expression, which continue to come from across the ideological spectrum. It shows that freedom for such expression remains an essential prerequisite for the equality, safety, and dignity of women and sexual/gender minorities.
Keywords: amériques; cours; discipline; droit; droits des femmes*; liberté d'expression; pornographie; premier cycle; régions géographiques; science politique et droit; sex wars; sex1911; thématiques; états-unis